REPRESENTASI SEJARAH DAN TRADISI KUNO BANYUMAS: ANTARA PERAN PEREMPUAN DAN PELESTARIAN ADAT OLEH NEGARA - Marwah, Sofa; Widyastuti, Tri Rini (History Department, Semarang State University and Historian Society of Indonesia, 2015)
This research-based paper aims at assessing the existence of female indigenous preservers in the preservation program of custom and culture by the state, and formulating the alternative model of preserving the custom and culture in Banyumas through strengthening the womens participation. This is necessary because the reality in the society shows that both women and men are equal to have the important role. In this case, the existence of women in Pekuncen, Kalisalak, Cikakak, Pasir Wetan and Gerduren is a representation of the synthesis between history, customs and Islamic values that colors the life of the local people. When the state enters the domain of the society and implements the program of preserving traditional villages, the existence of women is marginalized on account of being not directly involved. In fact, the actors of the traditional ceremonies such as unggah-unggahan, jaro rojab, gubrak lesung, rengkong and lengger, as well as the actors of the traditional cloth-making which is so-called lawon, are partly women.Keywords:Â women, preserving the custom, BanyumasPenelitian ini dimaksudkan untuk mengkaji eksistensi kaum perempuan pelaku adat di tengah program pelestarian adat istiadat dan budaya oleh negara, serta merumuskan alternatif model pelestarian adat istiadat dan budaya di Banyumas melalui penguatan partisipasi kaum perempuan. Hal ini diperlukan karena realitas di masyarakat menunjukkan bahwa perempuan dan laki-laki adalah pelaku adat yang sama-sama memegang peranan penting. Dalam hal ini, keberadaan kaum perempuan di Pekuncen, Kalisalak, Cikakak, Pasir Wetan dan Gerduren adalah representasi sintesa antara perjalanan sejarah, adat istiadat dan nilai-nilai Islam yang mewarnai sendi-sendi kehidupan masyarakat setempat. Ketika negara masuk dan melakukan program pelestarian desa adat, eksistensi kaum perempuan justru tergeser karena perempuan tidak dilibatkan secara langsung. Padahal pelaku upacara unggah-unggahan, jaro rojab, gubrak lesung, rengkong, lengger, pembuatan kain tradisional lawon, sebagiannya adalah perempuan.Kata kunci: perempuan, pelestarian adat, BanyumasÂ